Antimicrobial Activity of Nanoconjugated Glycopeptide Antibiotics and Their Effect on Staphylococcus aureus Biofilm - Berini, Francesca; Orlandi, Viviana Teresa; Gamberoni, Federica; Martegani, Eleonora; Armenia, Ilaria; Gornati, Rosalba; Bernardini, Giovanni; Marinelli, Flavia (Frontiers in Microbiology, 2021)
In the era of antimicrobial resistance, the use of nanoconjugated antibiotics is regarded as a promising approach for preventing and fighting infections caused by resistant bacteria, including those exacerbated by the formation of difficult-to-treat bacterial biofilms. Thanks to their biocompatibility and magnetic properties, iron oxide nanoparticles (IONPs) are particularly attractive as antibiotic carriers for the targeting therapy. IONPs can direct conjugated antibiotics to infection sites by the use of an external magnet, facilitating tissue penetration and disturbing biofilm formation. As a consequence of antibiotic localization, a decrease in its administration dosage might be possible, reducing the side effects to non-targeted organs and the risk of antibiotic resistance spread in the commensal microbiota. Here, we prepared nanoformulations of the ‘last-resort’ glycopeptides teicoplanin and vancomycin by conjugating them to IONPs via surface functionalization with (3-aminopropyl) triethoxysilane (APTES). These superparamagnetic NP-TEICO and NP-VANCO were chemically stable and NP-TEICO (better than NP-VANCO) conserved the typical spectrum of antimicrobial activity of glycopeptide antibiotics, being effective against a panel of staphylococci and enterococci, including clinical isolates and resistant strains. By a combination of different methodological approaches, we proved that NP-TEICO and, although to a lesser extent, NP-VANCO were effective in reducing biofilm formation by three methicillin-sensitive or resistant Staphylococcus aureus strains. Moreover, when attracted and concentrated by the action of an external magnet, NP-TEICO exerted a localized inhibitory effect on S. aureus biofilm formation at low antibiotic concentration. Finally, we proved that the conjugation of glycopeptide antibiotics to IONPs reduced their intrinsic cytotoxicity toward a human cell line.